'I've got a very dichotomous difference in the way that I perceive myself': Positive and negative constructions of body image following cancer treatment. (September 2019) - Grogan, Sarah; Mechan, Jayne; Persson, Sofia; Finlay, Sive; Hall, Matthew
This study investigated how women constructed body image following cancer. Four women, aged 32–67 years, who had experienced breast or bowel cancer took part in a 2-hour, in-depth focus group. Discourse analysis revealed that women orientated to positive aspects of the post-treatment body (silhouette, trust, acceptance) while acknowledging that their experiences were also traumatic (hair loss, scarring, sickness, swelling). Bodies and illness were concealed from public judgment, and women developed new trust in their bodies due to overcoming cancer; post-cancer bodies were accepted despite opportunities for normalisation. Implications for those wanting to support women during and after cancer are discussed.